2018
DOI: 10.1007/s00406-018-0888-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced oligodendrocyte density in layer 5 of the prefrontal cortex in schizophrenia

Abstract: Neuroimaging and post-mortem studies have implicated altered myelin integrity and oligodendrocyte abnormalities in the dysfunction of neuronal network in schizophrenia, including the prefrontal cortex, Brodmann area (BA) 10. Pyramidal neurons in layer 5 of BA10 are the important link of reciprocal frontal cortical-basal ganglia-thalamic circuits altered in schizophrenia. Previously, we found ultrastructural dystrophic and degenerative alterations of oligodendrocytes in layer 5 of BA10 in schizophrenia. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 67 publications
1
24
0
4
Order By: Relevance
“…Recently we have reported reduced oligodendrocyte density (-32%) in layer 5 of the PFC (Brodmann's area 10) in schizophrenia (12). In the present study we found dystrophic changes but no degeneration of oligodendrocytes in layer 5 of the PFC in schizophrenia.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Recently we have reported reduced oligodendrocyte density (-32%) in layer 5 of the PFC (Brodmann's area 10) in schizophrenia (12). In the present study we found dystrophic changes but no degeneration of oligodendrocytes in layer 5 of the PFC in schizophrenia.…”
Section: Discussionsupporting
confidence: 61%
“…These data suggest that neuroinflammation might be present in different subgroups of schizophrenia patients. Previously we found lowered oligodendrocyte density in layer 5 of the PFC in the schizophrenia patients (12). We hypothesized that oligodendrocyte dystrophy may be at least in part associated with increased activation of microglial cells located adjacent to dystrophic oligodendrocytes in the schizophrenia patients during acute psychosis.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Myelin structure that consists of the multi-lamella layer of plasma membranes formed by one of glia cells, oligodendrocyte, acts as the electrical insulator to control the saltatory conduction. A number of studies have demonstrated that myelin formation is also required for neuronal integrity, so that the defects of these structures cause neuronal and mental diseases, such as multiple sclerosis (MS) 4-8 , leukoencephalopathy 9 , and schizophrenia [10][11][12] . Pathological characteristics of some of these disorders in the spinal cord show that small diameter axons are more vulnerable, compared with large diameter axons 4,7 .…”
Section: Development Of Type I/ii Oligodendrocytes Regulated By Teneumentioning
confidence: 99%
“…In the entorhinal cortex of schizophrenia patients, we detected a decreased intensity of myelin basic protein (MBP) staining and found that decreased myelination correlated with disorganization of pre-alpha cells [3], demonstrating that disturbed neurodevelopment in these disorders might be the basis of disturbed myelin-based connectivity. In the gray matter of the prefrontal cortex, Kolomeets and Uranova report a reduction of the density of oligodendrocytes in schizophrenia [4]. Moreover, previous electron microscopy studies from that group in cases with very low postmortem intervals (time from death to autopsy) provided evidence for damaged myelin sheaths, myelin degeneration, and apoptosis/necrosis of oligodendrocytes in gray and white matter of the prefrontal cortex of patients with schizophrenia and affective disorders.…”
mentioning
confidence: 91%